'Every patient is like my child': pediatric neurosurgeons' relational and emotional bonds with their patients and families. (2nd January 2022) - Granek, Leeat; Shapira, Shahar; Constantini, Shlomi; Roth, Jonathan
Abstract: Purpose: To explore the relational and emotional components of the surgeon-patient relationship from the perspective of practicing pediatric neurosurgeons in the field. Materials and methods: The study utilized the Grounded Theory Method of data collection and analysis. 26 pediatric neurosurgeons from 12 countries were interviewed using video-conferencing technology. Results: Pediatric neurosurgeons find meaning, joy and pleasure in the relationships they form with their patients and their families, while also experiencing difficult and painful emotions when these patients do not do well. Four themes emerged from the analysis that include having a relational attachment to patients, forming bonds with the parents/caregivers of these patients, dealing with patient suffering, death and complications, and communicating bad news to parents. Conclusions: Pediatric neurosurgeons develop deep and enduring bonds with their patients and their families. These relationships are an integral part of what brings meaning and joy to their work, and simultaneously, are one of the most significant emotional challenges of their careers. . Training neurosurgical fellows should include pedagogical modules about the relational and emotional dimensions of their work, with a specific and dedicated focus on communicating bad news.